Implementation of an automatic monitoring system using electromagnetic induction parameters to enhance hot forging quality - Maulana, Gun Gun; Martawireja, Abdurrahman Harits; Suryatini, Fitria (Politeknik Negeri Lhokseumawe, 2025)
This research presents the implementation of an automatic monitoring system using electromagnetic induction parameters to enhance the quality of heating processes in hot forging industries. Efficient heating is essential in industrial applications, particularly during the production stage of hot forging. To ensure consistent product quality and optimize energy efficiency, accurate and responsive monitoring is required. The proposed system integrates electromagnetic induction sensors to capture, in real time, the physical characteristics of heated AISI 4140 Bolt M24 × 100 mm (±0.35 kg). Sensor data are processed using intelligent algorithms to identify critical parameters such as temperature, heat distribution, and optimal heating time. Based on these results, the system automatically adjusts heating parameters, thereby ensuring consistent product quality and improved energy efficiency. The results indicate that the system, supported by a Human–Machine Interface (HMI), Programmable Logic Controller (PLC), and infrared temperature sensors, was effectively implemented. It demonstrated real-time monitoring of process parameters with no detected errors, smooth data transfer between components, and reliable temperature display on the HMI with an average delay of only 1.1 seconds. This research provides an integrated solution to improve hot forging quality, reduce energy waste, and accelerate production cycles, contributing to more intelligent heating control systems for industrial applications.